Biocompatible Glasses From Bone Regeneration to Cancer Treatment - Marchi, Juliana (Advanced Structured Materials,, 2016)
This book focuses on the applications of bioglasses in the biomedical field. It starts with the history and evolution of bioglasses before moving on to the structure and percolation theory, and lastly investigating their current and potential future applications in various fields including dentistry, tissue engineering, bone regeneration, ophthalmology, and drug delivery. The chapters were written by a team of international experts in the field and will be of great interest not only to material scientists, but also to medical doctors and other health sector professionals.